Factors Determining The Behavioral Intention To Use Online Learning For English Language Learning Among Polytechnic Students - Suparman, Isyati (2023)
Due to the onset of the COVID-19 pandemic, the Emergency Remote Teaching (ERT) was enforced on learning institutions in Malaysia as a compulsory measure. Online learning approaches have been perceived as valuable for English for Second Language learning during the pandemic due to providing opportunities for students to continue their learning using digital tools. Similarly, the shift to fully online learning for teaching the English Language was also done in all Malaysian Polytechnics. However, there are insufficient studies in this context and how the sudden shift to online learning during the pandemic has influenced students’ attitude and intentions to use online learning specifically learning the English language. Therefore, to investigate factors that may influence students’ perception on their attitude and behavioral intention towards the use of online English language learning, a new model was proposed. The base-line model of the combined technology acceptance model and theory of planned behaviour (C-TAM-TPB) was revised by considering online technology use experience pre and post pandemic and online leaning anxiety. In addition, factors such as confidence in English and beliefs about second language learning were also considered as perceived behavioral control toward intention to use online learning specifically for the English Language.